AKTIVITAS PEDAGANG MAKANAN DISEKITAR OBJEK WISATA ISLAMIC CENTER DESA PEMATANG BERANGAN KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Eko Gasella; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The presence of merchants in the area of Islamic centere attractions can be said a very important role and required by visitor, daily Islamic Attractions center area has activities undertaken by the Islamic mosque Juma'ah center, with activities traders particularly food certainly takes a toll on the visitors and become comfortable Juma'ah , so that when they are hungry and need to eat, they do not need to be far out to buy them, so that they too could be running activities. Activities of local people (merchants) to attractions islamic center is how these traders by utilizing the courts new businesses that exist to be able to increase the income of their family economy, traders must be able to adapt to the crowds of visitors that if they can use will get a positive thing.This type of research is descriptive quantitative research. This research was conducted at the grand mosque in the area of national civil Rokan Hulu islamic center district. Pematang Berangan village, district Rambah, thestudy sample entire are food vendors that are planted in the study when researchers conducted interviewsat that time the number of traders who sell outside Region Attractions centere Islamic amounted to 15 people.Results from this study is the result of research Characteristics of merchants who sell Surrounding Attractions Causeway Village chestnut Islamic Center Rambah District of Rokan Hulu that traders were seen on age, education, gender, education, race, initial capital income, and capital resources. Factors that affect the income of traders who sell outside the area attractions Islamic centere is capital factor daily, factor working hours, factor in the type of goods be traded, and the factor of the length of selling / experience possessed by the merchant, and factors means trading a fifth of these factors affecting income food vendors who sell outside the area attractions Islamic centereKeywords: Activities, traders, Attractions Islamic center